Faktor-faktor penentu keterlambatan audit di Indonesia - Hendi, Hendi; Susanti, She Lee (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Submission of financial reports is very important to be done on time because delays in financial reporting are a negative thing for companies, especially for investors. The research uses a quantitative approach and secondary research data sources, including the company's annual report. This study examines the influence that can affect the occurrence of audit delays by examining the effect of audit complexity, audit opinion, international audit firms, company size, financial debt, profitability, and concentration of share ownership on audit delays. Tests were carried out on all 154 manufacturing category companies by analyzing data for the 2017–2021 period. The application of the method used is panel data regression. The results of this study indicate that audit delay is significantly influenced by audit complexity, audit opinion, company size, DER, ROA, and concentration of share ownership. Meanwhile, audit delays have no significant effect on international audit firms. The results of the F test simultaneously found that the independent variables had an effect on audit delays. The implications of this research can be a guide for controlling audit reporting or monitoring potential audit delays.